GABA-BZD Receptor Modulating Mechanism of Panax quinquefolius against 72-h Sleep Deprivation Induced Anxiety like Behavior: Possible Roles of Oxidative Stress, Mitochondrial Dysfunction and Neuroinflammation - Chanana, Priyanka; Kumar, Anil (Frontiers in Neuroscience, 2016)
ABSTRACT Rationale- Panax quinquefolius (American Ginseng) is known for its therapeutic potential against various neurological disorders, but its plausible mechanism of action still remains undeciphered. GABA (Gamma Amino Butyric Acid) plays an important role in sleep wake cycle homeostasis. Thus there exists rationale in exploring the GABA-ergic potential of Panax quinquefolius as neuroprotective strategy in sleep deprivation induced secondary neurological problems. Objective- The present study was designed to explore the possible GABA-ergic mechanism in the neuro-protective effect of Panax quinquefolius against 72-hours sleep deprivation induced anxiety like behaviour, oxidative stress, mitochondrial dysfunction, HPA-axis activation and neuroinflammation. Materials and Methods- Male laca mice were sleep deprived for 72-hours by using Grid suspended over water method. Panax quinquefolius (American Ginseng 50, 100 and 200 mg/kg) was administered alone and in combination with GABA modulators (GABA Cl- channel inhibitor, GABA-benzodiazepine receptor inhibitor and GABAA agonist) for 8 days, starting five days prior to 72-hours sleep deprivation period. Various behavioural (locomotor activity, mirror chamber test), biochemical (lipid peroxidation, reduced glutathione, catalase, nitrite levels), mitochondrial complexes, neuroinflammation marker (Tumour Necrosis Factor, TNF-alpha), serum corticosterone, and histopathological sections of brains were assessed. Results- 72-hours sleep deprivation significantly impaired locomotor activity, caused anxiety-like behaviour, conditions of oxidative stress, alterations in mitochondrial enzyme complex activities, raised serum corticosterone levels, brain TNFα levels and led to neuroinflammation like signs in discrete brain areas as compared to naive group. Panax quinquefolius (100 and 200 mg/kg) treatment restored the behavioural, biochemical, mitochondrial, molecular and histopathological alterations. Pre-treatment of GABA Cl- channel inhibitor as well as GABA-benzodiazepine receptor inhibitor, significantly reversed the protective effect of P. quinquefolius (100 mg/kg) in 72-hours sleep deprived animals (P<0.05). However, pretreatment with GABAA agonist, potentiated Panax quinquefolius’s protective effect which was significant as compared to their effect per se (p<0.05). Conclusion- GABA-ergic mechanism could be involved in the neuroprotective effect of P. quinquefolius against sleep deprivation induced anxiety-like behaviour, oxidative stress, mitochondrial dysfunction, HPA axis activation and neuroinflammation.